2002
DOI: 10.1097/00004347-200201000-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Panel of Immunohistochemical Stains, Including Carcinoembryonic Antigen, Vimentin, and Estrogen Receptor, Aids the Distinction Between Primary Endometrial and Endocervical Adenocarcinomas

Abstract: The histological distinction between a primary endometrial and a primary endocervical adenocarcinoma is often difficult, especially in small biopsy specimens. A preoperative distinction is important because primary surgical management differs between the two tumors. Cases of primary endometrioid endometrial (n=30) and primary endocervical (n=26) adenocarcinoma of endocervical type were stained immunohistochemically with the monoclonal antibodies against carcinoembryonic antigen (CEA), vimentin, estrogen recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
102
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(106 citation statements)
references
References 9 publications
3
102
0
1
Order By: Relevance
“…CEA has been touted as a good discriminatory marker for endometrial carcinoma vs histologic mimics, including endocervical carcinoma, [4][5][6][7]34 because endometrial carcinoma is usually CEA-negative and endocervical carcinoma is usually positive. Dallenbach-Hellweg et al, 5 however, reported that both endometrial and endocervical mucinous carcinomas expressed CEA; this was refuted by Kamoi et al, 9 who reported significantly more CEA expression in endocervical adenocarcinomas of the usual type compared to endometrioid adenocarcinomas of endometrium and endocervix and mucinous endometrial adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CEA has been touted as a good discriminatory marker for endometrial carcinoma vs histologic mimics, including endocervical carcinoma, [4][5][6][7]34 because endometrial carcinoma is usually CEA-negative and endocervical carcinoma is usually positive. Dallenbach-Hellweg et al, 5 however, reported that both endometrial and endocervical mucinous carcinomas expressed CEA; this was refuted by Kamoi et al, 9 who reported significantly more CEA expression in endocervical adenocarcinomas of the usual type compared to endometrioid adenocarcinomas of endometrium and endocervix and mucinous endometrial adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Morphologically similar carcinomas, such as endocervical adenocarcinomas, have been reported to express p16 [1][2][3] and carcinoembryonic antigen (CEA), [4][5][6] whereas endometrial adenocarcinomas frequently show estrogen receptor (ER), 7,8 progesterone receptor (PR), 7,8 and vimentin expression. 4,7,9 In practice, many pathologists have used immunohistochemical panels composed of markers against these antigens for determining site of origin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in keeping with other studies demonstrating a low frequency of hormone receptor expression in primary endocervical adenocarcinomas. [56][57][58][59][60][61] Metastatic endocervical adenocarcinomas in the ovary usually simulate either primary ovarian endometrioid tumors or mucinous tumors of gastrointestinal (not seromucinous/endocervical-like) type. The infrequent expression of hormone receptors in endocervical adenocarcinomas, lack of expression of hormone receptors in both primary ovarian atypical proliferative (borderline) mucinous tumors of gastrointestinal type and ovarian mucinous carcinomas of usual type in this study, and frequent expression of hormone receptors in ovarian endometrioid tumors observed in other studies 16,24,26,31 indicate that ER/PR expression is most often useful only in the distinction of endocervical adenocarcinomas from primary ovarian endometrioid but not mucinous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrioid adenocarcinomas of the uterine corpus usually exhibit cytoplasmic vimentin positivity. 5,6 Therefore, in those cases where the associated uterine tumour is endometrioid in type, vimentin staining may be of value in excluding tumour involvement of the cervix. Most other histological types of uterine carcinoma, including serous and clear cell, are vimentin negative.…”
Section: Discussionmentioning
confidence: 99%